An Inventory of Chiropteran Fauna in Bhubaneswar City, Eastern India - Subrat Debata; Sharat Kumar Palita (Bogor Agricultural University, Indonesia, 2018)
An inventory of chiropteran fauna was carried out in Bhubaneswar city, Odisha, eastern India during October 2015 and March 2016 following roost survey and mist net survey techniques. During the study a total 19 species of bats belonging to seven families including the nationally threatened Rhinolophus rouxii were recorded of which family Vespertilionidae was the most diverse one, represented by five species. Majority of 11 species are found roosting and breeding in old temples and caves and are vulnerable from renovation activities, persecution and tourism. Therefore, long term monitoring of these sites are essential to understand the population trend over time and derive appropriate conservation implications.